2018
DOI: 10.1186/s13002-018-0228-5
|View full text |Cite
|
Sign up to set email alerts
|

Survey of farmers’ knowledge of cassava mosaic disease and their preferences for cassava cultivars in three agro-ecological zones in Benin

Abstract: BackgroundCassava is an important crop in Africa that is widely cultivated for its starchy tuberous root, which constitutes a major source of dietary carbohydrates. Cassava mosaic disease (CMD) is the most devastating disease affecting cassava in Africa and causes enormous losses in yield. In Benin, specifically, cultivars resistant to CMD are not commonly planted, and even when CMD is observed in fields, farmers do not implement control measures, presumably because they lack proper knowledge and training. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 9 publications
5
21
0
Order By: Relevance
“…Our work supports numerous previous studies that have shown that culinary properties and taste of planting material is as important, if not more important, in planting material selection than properties of more economic traits such as yield, while the appearance of disease makes little to no difference on choice (Houngue et al 2018; Kombo et al 2012; Njukwe et al 2013; Ntawuruhunga et al 2007). With this in mind, efforts to use clean (and possibly also disease-resistant or tolerant) planting material to control disease epidemics need to address growers’ varietal preferences and needs (Evenson and Gollin 2003; Kiros-Meles and Abang 2008).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our work supports numerous previous studies that have shown that culinary properties and taste of planting material is as important, if not more important, in planting material selection than properties of more economic traits such as yield, while the appearance of disease makes little to no difference on choice (Houngue et al 2018; Kombo et al 2012; Njukwe et al 2013; Ntawuruhunga et al 2007). With this in mind, efforts to use clean (and possibly also disease-resistant or tolerant) planting material to control disease epidemics need to address growers’ varietal preferences and needs (Evenson and Gollin 2003; Kiros-Meles and Abang 2008).…”
Section: Discussionsupporting
confidence: 90%
“…Growers mostly recycle materials from their own fields, attributing this to variety preference as well as the fact that the material is readily available. The preference for recycling is supported by previous studies, which have shown that a majority of planting material is recycled within the same field, while a considerable portion is also exchanged with close friends or family (Chikoti et al 2016; Gnonlonfin et al 2011; Houngue et al 2018; Ntawuruhunga et al 2007; Teeken et al 2018). Although markets, organisations and middle-men are rarely involved in the movement of planting material, the large scale of the distances and quantities of material moved in each of these transactions highlighted by our study does indicate that they could be responsible for the movement of disease across large distances, which previous work has demonstrated could be severely detrimental to disease control (Legg et al 2014; McQuaid et al 2017a; McQuaid et al 2017b).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In the case of plant breeding, the direct involvement of farmers as an integral part of the process ensures the participation of the most important stakeholders in the breeding activities [ 6 , 7 ]. The objective of almost all the participatory breeding approaches has been to incorporate farmers’ knowledge and preferences into the breeding program in order to develop new varieties that will not be rejected by them [ 8 11 ]. Results of PRA studies are exploited in the identification of the parents to be crossed to develop new population for selection.…”
Section: Introductionmentioning
confidence: 99%
“…Cassava is the second staple food crop after maize in Benin Republic with 55% of farmers cultivating it [4]. However, the crop has major production constraints ranging from biotic to abiotic threats.…”
Section: Introductionmentioning
confidence: 99%